Inquiry-Based Learning on Students' Critical Thinking Skills at Aviation Vocational College - Fatmawati Sabur; Musri Kona; Yuyun Suprapto (Yayasan Keluarga Guru Mandiri, 2023)
This study aims to examine the influence of the Inquiry-Based Learning model on students' critical thinking ability in two locations, namely Makassar Aviation Polytechnic and Surabaya Aviation Polytechnic. The research sample consisted of 48 learners selected in total sampling. The research method used was a pretest-posttest design with a single group (one group pretest-posttest design). The data obtained were analyzed using an independent T-test. The results showed that simultaneously, the Inquiry-Based Learning model did not significantly influence students' critical thinking ability. It means that there are no other variables that can cause a decrease in the value of critical thinking ability (variable Y). However, it should be noted that this study was only conducted with one group with no comparison or control group, so the results may be limited in generalizing the results broadly. Thus, further research can be carried out by adding variables or the number of samples to deepen understanding of the Inquiry-Based Learning model's influence on students' critical thinking ability.